Seroprevalence of bovine viral diarrhea and neosporosis in cows in the region of Junín, Peru - Arauco V., Fernando (2015)
The seroprevalence of bovine viral diarrhea virus (BVDV) and neosporosis was estimated in 92 serum samples from cows in 12 farms in the Junín region. The cows did not have a history of vaccination against BVDV. Blood samples were collected from October to December 2013 and the detection of antibodies against BVDV and N. caninum was done through commercial blocking ELISA tests. Results showed that 16.3 ± 7.5% (15/92) and 3.3 ± 3.6% (3/92) of samples had antibodies against BVDV and N. caninum respectively. None of the cows was positive to both infections.